Strengthening Islamic Value of Rahmatan Lil Aalamin for Lampung Society by the Indonesian Ulema Council (MUI) - Amirudin, Amirudin; Romlah, Romlah; Yudha, Gesit (Universitas Islam Negeri Raden Intan Lampung, 2024)
The purpose of this study is to determine the role of the Indonesian Ulema Council (MUI) in promoting Rahmatan Lil Aalamin values in Lampung society, which is diverse in terms of ethnic, religious, and cultural backgrounds. The concept of Rahmatan Lil Aalamin, which teaches Islam as a mercy to all nature without regard for ethnicity, religion, or race, is particularly relevant in a pluralistic society like Lampung. This study employs a qualitative approach, with data gathered through in-depth interviews, participatory observation, and documentation studies. The findings revealed that MUI actively engages in educating the public about the value of tolerance, justice, and unity through various educational programs, seminars, and social media. MUI also works with other religious organizations to improve understanding of religious moderation and Rahmatan Lil Aalamin principles. Although challenges such as radicalization and differences in religious understanding persist, Lampung's local wisdom, such as cooperation and deliberation, demonstrates the application of these values. Women play an important role in shaping the character of a tolerant generation. This study suggests that MUI should continue to strengthen inter-organizational cooperation and tap into the potential of local wisdom to create a more harmonious and inclusive society in Lampung.